The conceptual model of collaborative economy - Hruška, Lubor; Krajčík, Vladimír; Formánek, Ivo (Univerzita Pardubice, 2018)
Sharing economy is a phenomenon which it is currently paid too much attention, both in positive and negative point of view. This concept is a relatively young in the economics, but the historical context of sharing principles can be observed from the beginning of the human community. The definition of a sharing economy requires a multidisciplinary approach for the complexity of the concept. The aim of the article is to introduce a new conceptual model of a sharing economy, which can be used in regulating of a part of sharing economy, which by its nature, causes unfair competition in the business environment, since traditional business models for the provision of the same services must bear the additional costs associated with the certification of services, safety training, etc.
Keywords: collaborative economy; sharing economy; new business models; J46; O17; R21; O33; O35; O38; P41; K20